TNF, TNF inducers, and TNFR2 agonists: A new path to type 1 diabetes treatment. Issue 1 (29th September 2017) - Faustman, Denise L.
Summary: In the past decade, interest in the century‐old tuberculosis vaccine, bacillus Calmette‐Guerin (BCG), has been revived for potential new therapeutic uses in type 1 diabetes and other forms of autoimmunity. Diverse clinical trials are now proving the value of BCG in prevention and treatment of type 1 diabetes, in the treatment of new onset multiple sclerosis and other immune conditions. BCG contains the avirulent tuberculosis strain Mycobacterium bovis, a vaccine originally developed for tuberculosis prevention. BCG induces a host response that is driven in part by tumour necrosis factor (TNF). Induction of TNF through BCG vaccination or through selective agonism of TNF receptor 2 (TNFR2) has 2 desired cellular immune effects: (1) selective death of autoreactive T cells and (2) expansion of beneficial regulatory T cells (Tregs). In human clinical trials in both type 1 diabetes and multiple sclerosis, administration of the BCG vaccine to diseased adults has shown great promise. In a Phase I trial in advanced type 1 diabetes (mean duration of diabetes 15 years), 2 BCG vaccinations spaced 4 weeks apart selectively eliminated autoreactive T cells, induced beneficial Tregs, and allowed for a transient and small restoration of insulin production. The advancing global clinical trials using BCG combined with mechanistic data on BCGs induction of Tregs suggest value in this generic agent and possible immune reversal of the type 1 diabetic autoimmune process.